Intensity-modulated radiotherapy for cervical esophageal squamous cell carcinoma without hypopharyngeal invasion: dose distribution and clinical outcome. (13th May 2019) - Ishida, Yuichi; Sakanaka, Katsuyuki; Fujii, Kota; Itasaka, Satoshi; Mizowaki, Takashi
Abstract: Hypopharyngeal invasion would be a key finding in determining the extent of the irradiation fields in patients with cervical esophageal squamous cell carcinoma (CESCC). This study aimed to investigate the clinical outcomes of chemoradiotherapy using simultaneous integrated boost intensity-modulated radiotherapy (SIB-IMRT) omitting upper cervical lymph nodal irradiation in CESCC without hypopharyngeal invasion, and the dosimetric superiority of SIB-IMRT to 3D conformal radiotherapy (3DCRT). We retrospectively identified 21 CESCC patients without hypopharyngeal invasion [clinical Stage I/II/III/IV (M1LYM); 3/6/5/7] (UICC-TNM 7th edition) who underwent chemoradiotherapy using SIB-IMRT between 2009 and 2015. SIB-IMRT delivered 60 Gy to each primary tumor and the metastatic lymph nodes, and 48 Gy to elective lymph nodal regions, including Levels III and IV of the neck, supraclavicular, and upper mediastinal lymphatic regions, in 30 fractions. The overall survival rate, locoregional control rate, and initial recurrence site were evaluated. 3DCRT plans were created to perform dosimetric comparisons with SIB-IMRT. At a median follow-up of 64.5 months, the 5-year locoregional control and overall survival rates were 66.7% and 53.4%, respectively. Disease progressed in eight patients: all were locoregional progressions and no patients developed distant progression including upper cervical lymph nodal regions as initial recurrence sites. The planning study showed SIB-IMRT improved target coverage without compromising the dose to the organs at risk, compared with 3DCRT. In conclusion, omitting the elective nodal irradiation of the upper cervical lymph nodes was probably reasonable for CESCC patients without hypopharyngeal invasion. Locoregional progression remained the major progression site in this population.